Measuring Time, Making History - Hunt, Lynn, 1945- (Book collections on Project MUSE., 2007)
Time is the crucial ingredient in history, and yet historians rarely talk about time as such. These essays offer new insight into the development of modern conceptions of time, from the Christian dating system (BC/AD or BCE/CE) to the idea of "modernity" as a new epoch in human history.